Calretinin expression in the mammalian neocortex: a review - Barinka, Filip; Druga, Rastislav (Physiological research, 2010)
In the mammalian neocortex, the calcium-binding protein calretinin is expressed in a subset of cortical interneurons. In the recent years, research on interneurons is one of the most rapidly growing fields in neuroscience. This review summarizes the actual knowledge of the functions of calretinin in neuronal homeostasis and particularly of the distribution, connectivity and physiological properties of calretinin expressing interneurons in the neocortex of rodents and primates, including humans. The possible neuroprotective role of calretinin and the presumed “resistance” of calretinin-expressing interneurons to various pathological processes are also discussed.
Keywords: S100 Calcium Binding Protein G; financování organizované; Animals; homeostáza; Mammals; Neocortex; Financing, Organized; Neurons; lidé; zvířata; savci; Homeostasis; neokortex; neurony; S100 kalcium vázající protein G; Humans